1988
DOI: 10.1152/ajpgi.1988.255.1.g113
|View full text |Cite
|
Sign up to set email alerts
|

Functional somatostatin receptors on a rat pancreatic acinar cell line

Abstract: Somatostatin receptors from a rat pancreatic acinar cell line, AR4-2J, were characterized biochemically, structurally, and functionally. Binding of 125I-[Tyr11]somatostatin to AR4-2J cells was saturable, exhibiting a single class of high-affinity binding sites (Kd = 0.55 +/- 0.06 nM) with a maximal binding capacity of 258 +/- 20 fmol/10(6) cells. Somatostatin receptor structure was analyzed by covalently cross-linking 125I-[Tyr11]somatostatin to its plasma membrane receptors. Gel electrophoresis and autoradiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0
1

Year Published

1990
1990
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 0 publications
3
22
0
1
Order By: Relevance
“…Pancreatic acinar cells, which do not synthesize SS but possess functional receptors for SS (48,58), may respond to SS produced in the pancreas by the D cells in the islets of Langerhans as well as to circulating SS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pancreatic acinar cells, which do not synthesize SS but possess functional receptors for SS (48,58), may respond to SS produced in the pancreas by the D cells in the islets of Langerhans as well as to circulating SS.…”
Section: Resultsmentioning
confidence: 99%
“…These observations have led to the suggestion that this peptide has a physiologically important function in the regulation of normal cell growth and that it might be a negative regulator of pancreatic acinar cell proliferation in vivo. SS exerts its physiological actions by interacting with membrane-bound receptors (48,58), which are coupled to adenylate cyclase (43), K' channels (61), voltage-dependent Ca*' channels (62), and tyrosine phosphatase (12). In addition, several authors have shown that SS increases the guanylate cyclase activity in several tissues (11,17,54).…”
Section: Guanylate Cyclase Somatostatin Receptors Somatostatin Like-imentioning
confidence: 99%
“…Functional receptors for substance P (Womack et al, 1985), CCK (Logsdon, 1986;Scemama et al, 1988), VIP and somatostatin (Viguerie et al, 1987(Viguerie et al, , 1988 have been reported to exist in AR4-2J cells. Stimulation of substance P receptors leads to an increase in amylase secretion, as confirmed in this work.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, CCK is reportedly able to increase or inhibit amylase secretion in AR4-2J cells (Scemama et al, 1988). Somatostatin receptors were found to be coupled to a Ni (Gj) protein and therefore on stimulation inhibit the VIP response (Viguerie et al, 1987(Viguerie et al, , 1988. Unless the relative density of these various receptors is established, it is not clear whether simultaneous stimulation of all receptors or Gproteins during the photodynamic action of SALPC would be expected to result in the inhibition or, as in normal cells, stimulation of amylase release (Matthews & Cui, 1989a, 1990.…”
Section: Discussionmentioning
confidence: 99%
“…Their performance was tested in vitro and in vivo using the well-characterized AR4-2J rat pancreatic cell line, 27 which exclusively expresses the SSTR2 subtype. 28 With this model, high clinical relevance can be expected because SSTR2 is the most abundant of all of the 5 SSTRs in human SSTR-expressing tumors 29 and because human and rat SSTR2 share 95% sequence homology.…”
mentioning
confidence: 99%